Rancang Bangun Low Power Pada Wireless Sensor Node Berbasis NRF24L01+ - Rachmat Eko Prasetyo; Sabriansyah Rizqika Akbar; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Currently, wireless technology is widely used given its ability in. Wireless technology is usually applied to monitor the environment with a long and has limited energy capacity. Consumption of energy in wireless technology becomes an important thing that must be considered because of the scarcity of energy will be higher if there is no action on energy savings. This research will create a management system on the wireless sensor node processor that is applied to Arduino Pro Mini and nRF24L01 + to reduce energy usage, so that energy usage is more efficient and reduces battery change periodically. The creation of this energy-efficient wireless node utilizes the standard architecture of a wireless sensor node by using the Arduino Pro Mini as a processor for data sensor acquisition, data transmission and energy regulation on wireless sensor nodes. For modules transmit data using nRF24L01 + because it requires low energy consumption to transmit data. In this study energy saving is done by changing the state of the processor on Arduino Pro Mini, nRF24L01 +, and both at once with the use of PA Level so that energy consumption in wireless sensor node will be lower. The results of this experiment showed the highest power of 87.66% using PA LEVEL and low power conditions against Arduino Pro Mini and nRF24L01 +.